ALTERNATIF MODEL PENGELOLAAN KEAMANAN DI DAERAH KONFLIK - Siregar, Sarah Nuraini (Jurnal Penelitian Politik, 2016)
In Post New Order era the security regulation has been rearranged and has caused a conceptual change of security and defense in Indonesia This can be seen through the regulation of separation of Polri and ABRI and accompanied by TAP APR No VI on seperation of TNI and Polri and TAP MPR VII in 2000 on the role of TNI and Polri These regulations have created a model of security management which arranged authority between TNI and Polri in conducting security management in conflict area particularly in Ambon Poso Aceh and Papua However these regulations have created new problems in the field especially related to regulation of duty and authority between Polri and TNI in handling security problems in conflict area Based on this illustration this study tries to analyse the implementation of state security management policy in conflict area and to recommend an alternative of security management model in conflict area along with other operational regulations in order to regulate strictly and clearly between function and authority of TNI and Polri in conducting security management in conflict area.